Effect of Water Clover Extract (Marsilea crenata Presl.) on the Diameter of the Staphylococcus epidermidis Inhibition Zone - Lud Waluyo; Arsya Lingga Datu; Mohammad Mirza Nuryady; Erni Yohani Mahtuti (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2025)
The incidence of acne in Indonesia reaches 85% with an age range of around 15-24 years. The research aims to analyze the effect of water clover extract (Marsilea crenata Presl.) on the inhibition zone of Staphylococcus epidermidis. This type of research is a true experiment with a quantitative approach. The experimental design is The Post Test-Only Control Group Design. The research population was a pure culture of Staphylococcus epidermidis and the sample used was Staphylococcus epidermidis with a density of 1.5 x 10-8. The research method is the well diffusion method. Data were analyzed using one-way analysis of variance (ANOVA). The results of the research were that the concentration of water clover extract (Marsilea crenata Presl.) 25% volume 30µl, 50µl, 75µl, and 100µl had an average diameter of the inhibition zone, namely 6.41 mm, 7.51mm, 8.36 mm, and 9.70 mm. The conclusion of this research is that there is an influence of water clover extract (Marsilea crenata Presl.) on the diameter of the inhibition zone of Staphylococcus epidermidis and the most effective concentration in inhibiting bacterial growth is 25% extract with a volume of 100 µl with an average diameter of the inhibition zone of 9.70 mm.